(untitled) (IAHS Medical Journal, 2026)
Background: Uretercele is a congenital abnormality affecting the urinary tract characterized by the cystic dilation of the ureter at its insertion point in to the bladder. The purpose of the study is to report experience of endoscopic electrosurgical treatment of ureterocele. Material and methods: This was a retrospective study conducted from January 2018 to December 2023 at Uttara Adhunik Medical College Hospital and in a Private Clinic in Dhaka, 45 patients with ureterocele were treated endoscopically. Data of these patients were analyzed retrospectively. Results: Patient age range 20-40 years and male female ratio was 20:25. Forty patient had unilateral ureterocele, stone in the uretrocele found in 5 patients. All the patients were underwent “Smiling mouth” electrosurgical meatotomy. Associated stone in the ureterocele was fragmented using pneumatic lithotripter. The mean duration of postoperative stay was 1-2 days, mean follow-up was 16 months. Postoperative successful decompression was evident in all patients. Non-obstructed pelvicalyceal system and improved renal parenchymal thickness observed in ultrasound among the follow-up of all patients. Conclusion: Endoscopic electrosurgical management of ureterocele can be done without any significant postoperative morbidity. Electrosurgical incision is effective in decompressing the ureterocele in long-term follow-up. It is a simple, minimally invasive and no need for any specialized costly instrument. IAHS Medical Journal Vol 8(1), June 2025; 35-38